2014
DOI: 10.1097/mou.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

What should we tell prostate cancer patients about (secondary) prevention?

Abstract: Purpose of review Briefly summarize the epidemiologic findings of selected lifestyle factors for prostate cancer progression, metastasis, or death, with a focus on behaviors after diagnosis where possible. We conclude by providing guidance on lifestyle practices that physicians may wish to prioritize for discussion with their patients. Recent findings Growing, but still limited, evidence suggests that lifestyle factors after prostate cancer diagnosis may impact prostate cancer-specific and overall morality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 44 publications
1
17
0
4
Order By: Relevance
“…Indeed, a recent study from our group showed that positive lifestyle changes, especially dietary modifications, occur after the diagnosis of prostate cancer and in other types of cancer in men [57]. Similar observations have also been reported by other investigators [58,59,60]. Studies have shown that a balanced diet may decrease the risk of chronic diseases such as hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Indeed, a recent study from our group showed that positive lifestyle changes, especially dietary modifications, occur after the diagnosis of prostate cancer and in other types of cancer in men [57]. Similar observations have also been reported by other investigators [58,59,60]. Studies have shown that a balanced diet may decrease the risk of chronic diseases such as hypertension and diabetes.…”
Section: Discussionsupporting
confidence: 83%
“…Primary care clinicians should provide regular evaluations of survivors to determine appropriate levels of participation in health promotion and lifestyle modification programs . Facilitators (eg, clinician and spousal involvement) and barriers to engaging in physical activity (eg, preexisting comorbidities) should be addressed and monitored prior to the initiation of behavior change programs.…”
Section: Guidelines For the Primary Care Management Of Prostate Cancementioning
confidence: 99%
“…Primary care clinicians should conduct routine assessments of body mass index among survivors across the prostate cancer survivorship continuum. For survivors who are overweight or obese, clinicians should recommend limiting the consumption of high‐calorie foods and beverages and promote weight loss activities such as increasing physical activity as they would do for patients without cancer.…”
Section: Guidelines For the Primary Care Management Of Prostate Cancementioning
confidence: 99%
“…Currently, the strongest evidence links obesity to poorer outcomes in cancer survivors, and this evidence is stronger for breast and prostate cancer [32–35,29,36] than for non-Hodgkin lymphoma [37,38]. It has not yet been established whether specific nutrients or food groups are associated cancer-related outcomes in survivors [32,39–41]. Studies suggest benefits of a diet high in fruits and vegetables, and low in saturated fats for breast and prostate cancer survivors [40,42,43].…”
Section: Discussionmentioning
confidence: 99%